Professor Bonnie Sue Lewis: Teacher, Scholar, and Missionary. ASM Lifetime Achievement Award 2025 - Robert, Dana L. (Missiology, 2026)
Introduction to Professor Bonnie Sue Lewis, upon her reception of the 2025 Lifetime Achievement Award of the American Society of Missiology.